Framework for Using Professional Engineering Tools to Develop Games in Post-Secondary Education - Maksims Kornevs; Harsha Krishna; Ibrahim Orhan (Serious Games Society, 2023)
Teaching is changing with increasing emphasis on teaching digitally to enable remote learning. While it gives more opportunities to engage students, it also makes it harder to learn professional skills, which is especially important for the engineering field. One problem might be the lack of professional tools for the digital education of engineers. The purpose of this work is to assess the feasibility of creating digital educational games by shaping professional tools themselves as games for post-secondary education, and to develop a framework for such a process. This article demonstrates a case for applying the proposed framework to develop a game for a communication network course using a computer network simulator. The findings of this work highlight the need to create such games in higher education based on professional tools.